UNDERSTANDING “LYING SPIRIT” IN 1 KINGS 22:22 - Gosal, Fellix; Tasane, Fiktor (Klabat Theological Review, 2025)
This research examines the concept of the "lying spirit" in 1 Kings 22:23 with a focus on its theological meaning and implications for understanding God's sovereignty and justice. In this passage, God is described as allowing a lying spirit to mislead Ahab's prophets as part of divine judgment. This phenomenon raises various questions about God's holy character amidst the use of lies to achieve His will. Through a historical-grammatical approach, linguistic analysis of the word רוּחַ (ruach), as well as a thematic study of divine sovereignty in the Old Testament text, this research finds that God's actions remain consistent with His just and righteous nature. God is not the originator of lies, but remains in His absolute authority, allowing humans to reap the consequences of their rejection of the truth. In addition, this research connects the relevance of this event to the challenges of integrity in a contemporary culture hit by the "post-truth" phenomenon. This research contributes to the study of Old Testament theology by offering a new perspective on the relationship between justice, truth, and divine sovereignty in ancient and contemporary contexts. Keywords: Spirit of Lying, 1 Kings 22:23, Sovereignty of God, Evil and Righteousness, Old Testament Theology